Abordajes conceptuales de la ecopedagogía en estudios mexicanos: una revisión sistematizada. : Abordajes conceptuales de la ecopedagogía - Paz Valdez, Angélica; Córdova Hernández, Juan Antonio; Lara Romero, Lily (Perspectivas Docentes, 2025)
The relationship that humans develop with their enviroment han given rise throughout history to the establishment of structures, influenced by factors such as colonialism and power hegemonies, create frameworks that translate into a fertile ground for the emergence issues that impacts in every way of living being in differents degrees. The current state of wold is known as a civilization crisis widely manifested in the extractivism of all elements that constitute life. In this article, we explore the various conceptual approaches of ecopedagogy, which serves as a response to the pressing need to move beyond environmental education. It emphasizes the importance of fostering reflections and actions amed at restructuring the currnt contiguration of human dynamics concerning economic, social and environmental aspects. This educational approach places critical thinking as its core and analyzes the ways we all navigate the planet.